O ensino da literatura no livro didático - MOTTES, Diana Vasconcelos (2023)
The present work seeks to do a qualitative research about the teaching of literature in the textbook, aiming to show how the literary text in the textbooks is being worked and how this teaching is developed in the classroom by the teachers, based on the vision of the selected theoretical assumptions for this job. It is advocated in favor of an early teaching of literature, with a view to a better apprehension of literary concepts by public school learners. In a first moment, the theories used will be presented and, in the sequence, the presentation of the corpus that will support the research, having as theoretical support thoughts of scholars who deal with this theme. It has to be added that the investigations of these practices are necessary, to understand how the techniques of teaching literature are given, since the teacher's support is the textbook. that literature be encouraged at school.